If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(4-(-5x-2)=30x+20
We move all terms to the left:
2(4-(-5x-2)-(30x+20)=0
| 9/2g=3/5 | | 6x+7=8x-1; | | x=3x^2-15x | | 2n-3=3n+3 | | 18x+252=4 | | 3x-6x(6+8)=7(7+3) | | 3x+4-x=4x-5 | | x-2x+8/3=1/4(x-2-x)-3 | | 6/4+2x=-2/x-10 | | 420÷d=30;d=15 | | 1/3x+1x=8 | | 7x+2(6x+15)=201 | | 2x+20=4÷7x | | 2=k4 | | 2=k1 | | (39/5)=2m | | -5=10-3n | | 90=2x+(4x-12) | | x-2x+8/3=1/4(x-2-x)/6-3 | | Z÷4+4=7-z÷4 | | 15x+2/16=0 | | -8x+14=-2(4x-7 | | (100-x)^2=0 | | 3/6z=6 | | -1(1/2)+v=-3(3/10) | | 3x+7=1+9x | | 1/2(4t-8)=t+8/4 | | 7-3x=54 | | 7.5*x=150 | | 8=1/2y | | 18/x+13=6/x-13 | | -7x-3=-66-2x |